2020
DOI: 10.2147/hiv.s255751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Immunological Response During HAART and Determinants of Current CD4<sup>+</sup> T-Cell Count Among HIV/AIDS Patients Attending University of Gondar Referral Hospital, Northwest Ethiopia</p>

Abstract: Purpose After the initiation of highly active antiretroviral therapy (HAART), successful HAART is characterized by an increase in the CD4 + count. Several factors affect the CD4 + T-cell count. This study aimed to assess the immunological response during HAART and determinants of the current CD4 + T-cell count among HIV/AIDS patients on HAART. Patients and Methods A hospital-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…67,68 In the current study, baseline CD4 + T-cell count was found to be significant, where for each increment of cells/ mm 3 of blood in the baseline CD4 + T-cell count, the current CD4 + T-cell count increased. This finding is consistent with studies conducted in Felege Hiwot referral hospital, 22 University of Gondar referral hospital, 21,69 and Tigray Health Research Institute. 23 The results of the current study have some limitations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…67,68 In the current study, baseline CD4 + T-cell count was found to be significant, where for each increment of cells/ mm 3 of blood in the baseline CD4 + T-cell count, the current CD4 + T-cell count increased. This finding is consistent with studies conducted in Felege Hiwot referral hospital, 22 University of Gondar referral hospital, 21,69 and Tigray Health Research Institute. 23 The results of the current study have some limitations.…”
Section: Discussionsupporting
confidence: 92%
“…The current CD4 + T-cell count of women of reproductive age on ART with poor adherence was less as compared with those with good adherence. Different studies conducted in China, 56 Abidjan, Côte d’Ivoire, 57 and University of Gondar Referral Hospital, northwest Ethiopia 21 , 58 revealed that adherence increased CD4 cells. Poor adherence to antiretroviral therapy (ART) may result in less effective viral suppression, poor immunological recovery, drug resistance, treatment side-effects, treatment failure, and subsequently reduced treatment options.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 33 On the other hand, for viral load testing, the plasma was prepared for transportation on dry ice to the Amhara Public Health Institute (APHI) and processed following the standard protocol and Biosafety precautions as described elsewhere. 34–36 At APHI, viral load was performed by using a quantitative real-time polymerase chain reaction (QRT-PCR) HIV-1 assay with the COBAS ® instrument (Roche, Homburg, Germany).…”
Section: Methodsmentioning
confidence: 99%